Efektivitas Penggunaan Realia Pada Penulisan Teks Deskripstif - Kiki Siti Fatimah (Holistik, 2022)
The purpose of this study was to determine whether or not there is the use of realia in class VIII SMP students. This research was conducted using experimental research and handled a quasi experimental design. The population of this study were students of class VIII SMP N 15 Cirebon. Researchers took samples from class VIII A as an experimental class consisting of 33 students and VIII B as a control class consisting of 33 students. The experimental class was taught using realia media in descriptive text and the control class was taught using conventional strategies (without using realia media). Data analysis was calculated statistically with SPSS 20. The results showed that t count> -t table or -11.455 and df (degrees of freedom) N-1 = 32 at the 0.05 degree of significance, the t-table was 2.037. So t-count> t-table - 11.455> 2.037 then t-count is higher than t-table. So H0 (null) is rejected. Then Ha (alternative) is accepted. So, the researchers found that the use of realia media for students' writing skills in descriptive text for class VIII at SMP N 15 Cirebon was effective after the researcher conducted research in the 2018/2019 academic year. It appears that students' writing has a significant influence on the use of realia media.